Modeling and analysis of coagulated liver tissue and its interaction with a scalpel blade. - Leong, Florence; Huang, Wei-Hsuan; Chui, Chee-Kong (Medical & Biological Engineering & Computing, 2013)
Radiofrequency-assisted methods have been used in hepatectomy--the resection process of removing liver tissue which encapsulates the tumor from the liver organ. A prototype was built to enable smooth surgical transition between radiofrequency ablation and liver resection. There is a lack of literature on mechanical properties of radiofrequency-ablated liver tissue and the tool-tissue interaction during cutting. This led to our study on coagulated tissue mechanical properties and modeling of its dynamic interaction with a scalpel blade. A novel mechanical model was proposed to mimic the mechanical behavior of radiofrequency-ablated liver tissue. The model is able to account for the viscoelastic behavior of the ablated tissue in both compression and relaxation tests. Experiments were performed to validate the proposed model. In addition, a knife blade-tissue interaction model is proposed to demonstrate the potential of integrating the proposed model for application in device design.